2017
DOI: 10.1016/j.urology.2016.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparity in Treatment for Prostate Cancer: Does Cancer Severity Matter?

Abstract: Objectives To determine if there are variations in the receipt of treatment based on race and disease severity. Treatment variations in men with prostate cancer among the various racial groups in the US exist, which may be a source of potential disparity in outcome. Methods Utilizing Surveillance, Epidemiology and End Results (SEER) -17, we identified 327,636 men diagnosed with prostate cancer from 2004–2011. Logistic regression analysis was performed to determine the association of receiving definitive trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 30 publications
2
54
1
Order By: Relevance
“…The current study observed that race/ethnicity, neighborhood SES, and Medicaid/public insurance were significantly associated with use of orchiectomy over medical forms of ADT. These results are consistent with prior research suggesting that the choice of 2 treatments for prostate cancer that have identical efficacy may differ based on social factors such as SES, insurance, and race/ethnicity …”
Section: Discussionsupporting
confidence: 91%
“…The current study observed that race/ethnicity, neighborhood SES, and Medicaid/public insurance were significantly associated with use of orchiectomy over medical forms of ADT. These results are consistent with prior research suggesting that the choice of 2 treatments for prostate cancer that have identical efficacy may differ based on social factors such as SES, insurance, and race/ethnicity …”
Section: Discussionsupporting
confidence: 91%
“…At the same time, among all AA and white men who perceived their cancers to be aggressive, there were no racial differences in treatment received. Taken together, these findings suggest that the misalignment between perceived cancer aggressiveness and actual diagnosis among AA and white men may contribute to the differences in treatments described by prior studies …”
Section: Discussionmentioning
confidence: 61%
“…In a study by Moses et al using the Surveillance, Epidemiology, and End Results database of patients diagnosed with prostate cancer across the United States, AA men were less likely to receive treatment (radical prostatectomy [RP], external‐beam radiation therapy [RT], or brachytherapy) in comparison with white men. Moreover, AA men received less aggressive treatment (ie, less surgery and more radiation): 31.0% of AA patients and 38.2% of white patients underwent RP, whereas 26.8% of AAs and 22.7% of whites underwent RT . Although published studies have consistently described less treatment overall and less aggressive treatment among AA men with prostate cancer, the reasons behind this disparity are not well understood, and few studies have examined the factors influencing patients’ decisions that may contribute to this disparity …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, racial disparities and barriers to care among AA patients applied to the use of definitive therapy for localized PCa . This phenomenon affected the rates of RP, which were lower in AAs than in NHWs . A similar phenomenon was recorded for rates of LND at RP.…”
Section: Introductionmentioning
confidence: 76%
“…Several investigators showed racial disparities in the quality of care for localized PCa . Specifically, racial disparities and barriers to care among AA patients applied to the use of definitive therapy for localized PCa .…”
Section: Introductionmentioning
confidence: 99%